2002
DOI: 10.1108/08880450210415716
|View full text |Cite
|
Sign up to set email alerts
|

Library fee‐based information services: financial considerations

Abstract: Fee‐based services in libraries offer research and document delivery services to non‐primary clientele on a cost‐recovery basis. Highlights services at the University of Colorado, Boulder, Rice University and Purdue University. Explores the major financial considerations involved in starting a new fee‐based service, including planning, staffing, pricing and marketing. Relates several special opportunities to which the libraries could not have responded without having had an existing fee‐based service with expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
0
9
0
4
Order By: Relevance
“…Most of the existing literature [38]- [43], while revealing user behavior before and after fees are introduced, does not come to any resounding conclusions about whether or not fees are detrimental to venue use. One work that illustrates this is Egholm and Jochumsen's article, Perceptions Concerning User Fees in Public Libraries [40].…”
Section: Literature Reviewmentioning
confidence: 93%
“…Most of the existing literature [38]- [43], while revealing user behavior before and after fees are introduced, does not come to any resounding conclusions about whether or not fees are detrimental to venue use. One work that illustrates this is Egholm and Jochumsen's article, Perceptions Concerning User Fees in Public Libraries [40].…”
Section: Literature Reviewmentioning
confidence: 93%
“…This is based on the fact that the library is a non-profit organization (Ubogu & Okiy, 2011). Notwithstanding, it is clear that most university libraries, especially in Nigeria and other developing nations are instituting fees on some services offered, as a means of generating revenue and additional income to augment the meagre annual disbursement they receive from their parent institutions (Nnadozie, 2013;Ward, Fong & Camille, 2002). In addition, these fee-based services can effectively serve as a way of meeting the existing needs of library users and delivering new/modern library services (Jenda, 2000).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Furthermore, Igbokwe, Ezeji and Obidike (2010) study on problems militating against marketing of library services in selected Nigerian libraries revealed that the major fee-based services were binding and photocopy while the free services were compilation of bibliography and retrospective services. This is because fee-based services not only ensure additional income generation but goes further to indirectly improve the services of the library as well as increase its ability to procure the relevant facilities and in so doing improve users satisfaction (Nnadozie, 2013;Jenda, 2000, Obodoeze, 2007Ward, Fong & Camille, 2002). Furthermore, Anyaoku (2009) believes that fee-based services have been advocated and accepted as the panacea to the economic depression in libraries.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…They were often designed to serve the needs of external users wanting specific services, such as ILL (Ward and Camille 2002), or subject specific reference assistance, for example in business (Ernest, 1993). And while some feebased services have come and gone, others persist, such as University of Minnesota Libraries' InfoNOW service (2016).…”
Section: Project 2: Specialized Library Services Pilotmentioning
confidence: 99%